VARIABILITY OF WATER MASS TRANSPORT IN KARIMATA AND GASPAR STRAITS DURING 2010-2014 AND ITS CONTRIBUTION TO INDONESIAN THROUGHFLOW (ITF) - Pramesti Anwar, Iwan
The Karimata Strait, which is located between Kalimantan and Belitung Islands and the Gaspar Strait, which is located between Belitung and Bangka Islands, are straits traversed by transport of water masses originating from the South China Sea. In this study, the variability of water masses in these straits is assessed through their transport of volume, heat, and freshwater, both temporally and spatially. Data used in this study is obtained from the simulation results of 3-D HAMburg Shelf Ocean Model (HAMSOM) for 5 years from 2010 to 2014 in a model domain between 1° 0' 0'' - 4° 30' 0'' S and 104° 0' 15'' - 110° 30' 0'' E with horizontal resolution of 0.5 '(approx. 0.94 km). The simulation results have been compared to measurement data from June 26, 2012 to April 30, 2014 of South China Sea - Indonesian seas Transport/Exchange (SITE) Project. The root mean square error of volume, heat, and freshwater transports between model and measurement in the Karimata Strait are 0.01 Sv, 0.05 PW, and 0.02 Sv, respectively. Meanwhile in the Gaspar Strait are 0.01 Sv, 0.02 PW, and 0.018 Sv, respectively. The daily mean of volume, heat, and fresh water transport is -0.37 Sv, -0.036 PW, and -0.025 Sv for Karimata Strait and -0.21 Sv, -0.015 PW, and -0.021 Sv for Gaspar Strait, where negative sign indicates southward transport, 1 Sv = 106 m3/s, and 1 PW = 1015 W. By applying an Empirical Orthogonal Function (EOF) to the data of water mass transport, five main modes with variances of 96.43%, 1.33%, 0.75%, 0.53%, and 0.17% for Karimata Strait and 96.84%, 1.62%, 0.42%, 0.27%, and 0.18% for Gaspar Strait are obtained. The first mode explains the annual cycle (365 days), while the second to fourth modes explain the intraannual cycle (183, 122, and 122 days), and the latest mode explains the interannual cycle (608 days). The average transport of volume, heat, and freshwater in the Karimata and Gaspar Straits that influenced the ITF based on 5 years simulation results are -0.3 Sv and -0.02 Sv, -0,03 PW and -0,02 PW, and -0,019 Sv and -0,014 Sv, respectively.